Management of the Deviated Nasal Dorsum - Loyo, Myriam; Wang, Tom D. (Facial Plastic Surgery, 2015)
The deviated nasal dorsum veers off the ideal straight vertical orientation at midline. Deviations in the dorsum lead to functional and aesthetic consequences that frequently prompt the patient to seek consultation with a rhinoplasty surgeon. Inability to breathe through the nose and self-image perception significantly detracts from the patient's quality of life. Correction of the deviated nasal dorsum represents a challenge for the rhinoplasty surgeon. Anatomic correction of deviations is the goal. Straightening a deviated nasal dorsum will require maneuvers to realign the nose distinct from traditional aesthetic rhinoplasty techniques. The nasal dorsum is formed by the three-dimensional structures of the septum, the bony nasal pyramid, and the cartilaginous nasal midvault. Restoring the position of the septum at midline is the first step in providing adequate support to the nasal architecture. Extracorporeal septoplasty and anterior septal transplant are often necessary techniques to correct the septum and achieve dorsal correction. Subsequently, asymmetric maneuvers to bony dorsum and midvault are performed to restore symmetry. Asymmetric hump reduction and nasal osteotomies are often necessary. Supporting the midvault to avoid nasal collapse often requires asymmetric maneuvers to the upper lateral cartilages and asymmetric spreader grafts. Finally, camouflaging grafts to the nasal dorsum may be necessary. Significant rigidity and memory of the native tissues must be overcome to successfully straighten a nose. The surgeon who can master the deviated dorsum will significantly improve the appearance and quality of life of the patients he or she treats.
Keywords: deviated nasal dorsum; crooked nose; straightening rhinoplasty; anterior septal transplant; intermediate osteotomy